Patients' views on electronic patient information leaflets - Hammar T; Nilsson AL; Hovstadius B. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Information in society and in health care is currently undergoing a transition from paper to digital formats, and the main source of information will probably be electronic in the future. Objective: To explore patients' use and perceptions of the patient information leaflet included in the medication package, and their attitude towards a transition to an electronic version. Methods: The data was collected during October to November 2014 among individuals in South-Eastern Sweden, using a questionnaire (n=406, response rate 78%) and interviews (n=15). Results: The questionnaire showed that the majority of the respondents (52%) occasionally read the patient information leaflet, 37% always read it, and 11% never read it. Almost half of the patients (41%) were positive towards reading the patient information leaflet electronically while 32% were hesitant and 26% neutral. A majority of the patients would request to get the patient information leaflet printed at the pharmacy if it was not included in the package. There were differences in attitude related to age and gender. The interviews showed that patients had mixed views on a transition to an electronic patient information leaflet. The patients perceived several positive aspects with an electronic patient information leaflet but were concerned about elderly patients. Conclusion: Although many were positive towards reading the patient information leaflet electronically, the majority prefer the patient information leaflet in paper form. Providing appropriate and useful eHealth services for patients to access the patient information leaflet electronically, along with education, could prepare patients for a transition to electronic patient information leaflet.